Cyanophycean Algae Inhabiting Sodic Soil Exhibit Diverse Morphology: An Adaptation to High Exchangeable Sodium - Singh, P. K.; Kishore, S.; Prakash, J.; Singh, S. K.; Shukla, M. (Ecoprint: An International Journal of Ecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A soil pot experiment was conducted in soils containing two exchangeable sodium percentage (ESP) levels i.e. normal (4.37) and high (54.5) ESP levels. The soils used in experiment were collected from different natural conditions to asses the algal biodiversity and changes in morphology of algae. The genera reported at high ESP were Oscillatoria, Lyngbya and colony of Anabaena while in normal soil these were absent. The heterocyst chain was also observed in soil of high ESP while in normal soil it was not reported. The width of heterocyst was much different than those reported. The chemical properties of soil e.g. pH, exchangeable sodium and ESP were decreased while organic carbon and total nitrogen contents were increased after one year algal growth. Key words: Cyanophycean algae, heterocyst, sodic soil, exchangeable sodium percentage. doi: 10.3126/eco.v15i0.1937 ECOPRINT 15: 15-21, 2008